Ancient human genome sequence of an extinct Palaeo-Eskimo - Rasmussen, M.; Li, Y.; Lindgreen, S.; Pedersen, J.; Albrechtsen, A.; Metspalu, M.; Metspalu, E.; Kivisild, T.; Gupta, R.; Bertalan, M.; Nielsen, K.; Gilbert, Thomas; et al. (Nature Publishing Group, 2010)
We report here the genome sequence of an ancient human. Obtained from,4,000-year-old permafrost-preserved hair, thegenome represents a male individual from the first known culture to settle in Greenland. Sequenced to an average depth of203, we recover 79% of the diploid genome, an amount close to the practical limit of current sequencing technologies. Weidentify 353,151 high-confidence single-nucleotide polymorphisms (SNPs), of which 6.8% have not been reportedpreviously. We estimate raw read contamination to be no higher than 0.8%. We use functional SNP assessment to assignpossible phenotypic characteristics of the individual that belonged to a culture whose location has yielded only trace humanremains.We compare the high-confidence SNPs to those of contemporary populations to find the populations most closelyrelated to the individual. This provides evidence for a migration from Siberia into the New World some 5,500 years ago,independent of that giving rise to the modern Native Americans and Inuit.